Antarctic Circumpolar Current Dynamics at the Pacific Entrance to the Drake Passage Over the Past 1.3 Million Years. Issue 7 (9th July 2020) - Toyos, María H.; Lamy, Frank; Lange, Carina B.; Lembke‐Jene, Lester; Saavedra‐Pellitero, Mariem; Esper, Oliver; Arz, Helge W.
Abstract: The Antarctic Circumpolar Current (ACC) is the world's largest current system connecting all three major basins of the global ocean. Our knowledge of glacial‐interglacial changes in ACC dynamics in the southeast Pacific is not well constrained and presently only based on reconstructions covering the last glacial cycle. Here we use a combination of mean sortable silt grain size of the terrigenous sediment fraction (10–63 μm, SS ¯ ) and X‐ray fluorescence scanner‐derived Zr/Rb ratios as flow strength proxies to examine ACC variations at the Pacific entrance to the Drake Passage (DP) in the vicinity of the Subantarctic Front. Our results indicate that at the DP entrance, ACC strength varied by 6–16% on glacial‐interglacial time scales, yielding higher current speeds during interglacial times and reduced current speeds during glacials. We provide evidence that previous observations of a reduction in DP throughflow during the last glacial period are part of a consistent pattern extending for at least the last 1.3 Ma. The orbital‐scale cyclicity follows well‐known global climate changes from prevailing ca. 41‐kyr cycles in the early part of the record (1.3 Ma to 850 ka; marine isotope stage 21) across the mid‐Pleistocene transition into the middle and late Pleistocene 100‐kyr world. A comparison to a bottom water flow record from the deep western boundary current off New Zealand (Ocean Drilling Program Site 1123) reveals anti‐phased changes between the two sites. The enhanced supply of deep water along the DP and into the Atlantic Ocean during interglacials corresponds to a weakened flow of the SW Pacific deep western boundary current. Key Points: The strength of ACC flow in the SE Pacific varied strongly on glacial‐interglacial time scales Over the past 1.3 Ma, our results show a consistent pattern of stronger (weaker) flow during interglacials (glacials) The sortable silt record largely follows orbital‐scale cyclicity, changing from ca. 41‐kyr cycles into a 100‐kyr world after the MPT